Effectiveness of KWL (Know-Want-Learn) Thinking Strategy to Learning Activity and Understanding of Living Creature Classification Concepts - Umi Farida; Retno Sri Iswari; Dyah Rini Indriyanti (Journal of Innovative Science Education, 2020)
Science is a learning given at school. Learning strategy choices would influence to learning success. There is a need of creative and innovative strategy to improve learning activities and student conceptual understanding, such as by using KWL thinking strategy (Know-Want-Learn) assisted by video. This research aims to analyze learning activity and effectiveness of learning conceptual understanding at VII grade of a Public Junior High School in Nganjuk after being intervened by KWL thinking strategy assisted by video. This quasi experimental research design used pretest-posttest control group design with 64 students in which 32 of them grouped into control group while the remaining were grouped into experimental group. Technique of collecting data was simple random sampling.